Determinants of Customer Relationship Marketing of Mobile Services Providers in Sri Lanka: - An application of Exploratory Factor Analysis - Velnampy, T.; Sivesan, S. (My University, 2012)
Customer relationship marketing is very important concept to attract and keep the customers in organizations. In modern business world, marketing focus reflect the move away from transactional marketing to relationship marketing. There are no comprehensive and empirical researches in that field especially in mobile service. Data was collected through a seven points Likert type summated rating scales of questionnaires from strongly disagree to (1) to strongly agree (7) were adopted to identify indicators. Sophisticated statistical model as “Exploratory Factor Analysis” (EFA) has been used. The results show three factors extract from the analysis that together accounted 67.007% of the total variance. These factors were categorized as trust, rapport, and accuracy.
Keywords: Customer relationship marketing; Trust; Rapport; Accuracy